2018
DOI: 10.1094/pdis-04-17-0547-re
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance and Economics of Yield Loss Associated With Angular Leaf Spot Disease of Common Bean in the Southern Highlands of Tanzania

Abstract: Angular leaf spot (ALS) caused by Pseudocercospora griseola is among the devastating diseases of common bean (Phaseolus vulgaris L.) in the Southern Highlands of Tanzania (SHT). This study was conducted to assess the agronomic performance and economics of yield loss associated with the disease on five bean cultivars that are widely grown by farmers. The cultivars were evaluated in a split plot design with a randomized complete block arrangement during 2012/2013 and 2013/2014. The main plots were two rates of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In a fungicide study on the control of angular leaf spot [Pseudocercospora griseola (Sacc.) Crous & Braun] of dry beans in Tanzania, Mongi et al (2018) demonstrated that the yield components of various treatments were strongly influenced by the amount of rain received during the growing season because of its influence on disease development. Habtu and Zadoks (1995) speculated that the effect of bean rust [Uromyces appendiculatus (Pers.)…”
Section: Discussionmentioning
confidence: 99%
“…In a fungicide study on the control of angular leaf spot [Pseudocercospora griseola (Sacc.) Crous & Braun] of dry beans in Tanzania, Mongi et al (2018) demonstrated that the yield components of various treatments were strongly influenced by the amount of rain received during the growing season because of its influence on disease development. Habtu and Zadoks (1995) speculated that the effect of bean rust [Uromyces appendiculatus (Pers.)…”
Section: Discussionmentioning
confidence: 99%
“…The increase in land acreage under common bean production by farmers attempting to meet the increasing local and regional demand has been challenged by many abiotic and biotic stresses [20], of which insect pests [21] and diseases including angular leaf spot [7], common bacterial blight [22], anthracnose and root rots [23] are major. The effects of the numerous pests and diseases range from mild symptoms to severe plant damages, which normally result in significant yield losses [10] [24]. To increase the yield and production of common beans by the majority small-holder farmers, integration of effective and economically viable resources or practices for management of the abiotic and biotic constraints is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Angular leaf spot is major disease in the sub-Saharan regions where it has caused yield losses of 61% [24].…”
Section: Discussionmentioning
confidence: 99%
“…A yield loss that reached up to 80% had been reported on susceptible common bean genotypes under severe conditions of infection [6]. Mongi [13], reported yield losses of up to 61% in Southern Tanzania. Stenglein et al [14], reported that for every 10% increase in ALS severity results in 7.9% yield loss.…”
Section: Angular Leaf Spot (Als)mentioning
confidence: 96%